Spark erosion machining behaviour of coconut shell ash reinforced silicon metal matrix. (2020) - Mohan Babu, P.; Rajamuneeswaran, S.; Pritima, D.; Marichamy, S.; Vairamuthu, J.
Abstract: In recent days, the production of a metal matrix with excellent properties is a challenging task. The contribution of silicon in industries particularly, the demand is increased in electronics industries. The quality of the metal matrix is focused on new reinforcements and composition. In this concept, coconut shell ash is applicable as a strengthening element. It has accumulated on silicon using stir cast. The composite is machined by Spark Erosion Machining (SEM) after the evaluation of substance properties. The Material Subtraction Rate (MSR) is determined to change the control parameters. The MSR is enhanced through graphite mixed dielectric fluid. The maximum MSR and its optimal parameters are found through Taguchi optimization.